Marital Satisfaction and Father Involvement on Company X's Employees: The Role of Workplace Flexibility - Somantri, Siti Dara Futri; Riasnugrahani, Missiliana; Setiawan, Tery (TAZKIYA Journal of Psychology, 2024)
Father involvement has a positive impact on children's cognitive, emotional and social development. However, the level of this involvement is low in the Asian context, particularly in Indonesia, where traditional gender roles often reduce paternal involvement. The role of fathers in children's development is increasingly recognized, but there remains a research gap in understanding how factors such as marital satisfaction and workplace flexibility jointly influence fathers' involvement. This research aims to determine the moderating role of workplace flexibility on the relationship between marital satisfaction and father involvement with surveyed fathers who work at Company"X", have children aged 1-21, live with their children and their wife. This research was conducted to 123 respondents. Measurement tools used in the research include the Father Involvement Inventory (IFI), the ENRICH Marital Satisfaction Scale, and the Workplace Flexibility Scale. Each measurement instrument has been tested for validity and reliability. The data analysis technique used is Moderation Process Analysis: Model 1 of Hayes (2013) using the SPSS Statistics program version 29. Based on the hypothesis testing results, there is a significant role of marital satisfaction on father involvement at 33%, but workplace flexibility does not moderate the relationship between marital satisfaction and father involvement. Demographic factors in this research also do not play a role in father involvement. These findings highlight the important role of marital satisfaction in promoting fathers' active participation, suggesting that improving marital relationships may be more effective than simply increasing workplace flexibility in encouraging fathers to become involved with their children. These results could also be interesting for exploring other factors likely to predict father involvement.